KAN TERAPEUTEN ÆNDRE PATIENTENS PSYKE? - Diderichsen, Birgitte (Psyke & Logos, 2022)
The article discuses the psychoanalytic concept of resistance. Freud defined resistance as a clinical concept which is crucial in respect to the potential change of the patient's personality brought about by analytic treatment. Resistance is mobilized in the therapy because it has its origin in the same motives which created the patient's problems. In his last years Freud saw resistance as the patient's attempts to protect his weak ego. The article discusses this point of view from the perspective of Ferenczi's analysis ofthe so-called character disorders and in perspective of modern psychoanalysis it is discussed whether resistance must be understood as a phenomena, which is not only connected to the patient, but is created by the therapeutic relation and has to do with the therapist's attitude to the patient. A point of view, which has crucial consequences for the therapeutic technique.